1994
DOI: 10.1152/jappl.1994.77.2.767
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hyperoxia at 1 and 2 ATA on hypoxia and hypercapnia in human skin during experimental inflammation

Abstract: Transcutaneous PO2 and PCO2 measurements and estimates of skin respiration were monitored at different levels of inspired PO2 in 20 healthy adults during the first 4 days of the tuberculin reaction, a convenient model of acute inflammation. Hyperoxia at 1 and 2 ATA significantly increased transcutaneous PO2 levels in undisturbed and in inflamed skin but did not fully correct the relative hypoxia at the site of inflammation. Hypercapnia was reduced with O2 breathing at 2 ATA. The apparent rate of O2 consumption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…To date, the exact regulatory mechanisms that govern local tissue oxygenation in L.-infected tissues are unknown. In L. major-infected tissues of resistant C57BL/6 mice, transient infection-induced metabolic oxygen demands (Campbell et al, 2014) and/or transient impairment of local tissue perfusion (Abbot et al, 1994;Melican et al, 2008;Massberg et al, 2010) might contribute to the low oxygen values. It is tempting to speculate that in mice displaying a non-healing phenotype (such as BALB/c mice) the NOdependent anti-leishmanial activity of lesional macrophages may be continuously extinguished, because pO 2 on the site of infection might not return to normal levels (as in C57BL/6 healer mice).…”
Section: Discussionmentioning
confidence: 99%
“…To date, the exact regulatory mechanisms that govern local tissue oxygenation in L.-infected tissues are unknown. In L. major-infected tissues of resistant C57BL/6 mice, transient infection-induced metabolic oxygen demands (Campbell et al, 2014) and/or transient impairment of local tissue perfusion (Abbot et al, 1994;Melican et al, 2008;Massberg et al, 2010) might contribute to the low oxygen values. It is tempting to speculate that in mice displaying a non-healing phenotype (such as BALB/c mice) the NOdependent anti-leishmanial activity of lesional macrophages may be continuously extinguished, because pO 2 on the site of infection might not return to normal levels (as in C57BL/6 healer mice).…”
Section: Discussionmentioning
confidence: 99%
“…HBOT has been shown to possess potent anti-inflammatory properties in both animal [55,67,68] and human studies [10,11,20,46,69] and has been reported to decrease the production of pro-inflammatory cytokines (such as TNF-alpha, interferon-gamma, IL-1 and IL-6) in both animal [66,70] and human studies [20,49] as well as increase IL-10 levels [71]. Several of the reviewed studies (including human studies and animal models) reported a decrease in inflammation as measured by reduced tissue edema and histopathological changes, as well as a decrease in TNF-alpha, IL-1 and IL-6 with HBOT [49,54,61,63,66].…”
Section: Discussionmentioning
confidence: 99%
“…by accumulation of inflammatory cells, more than the local blood flow, which leads to lactic acid accumulation (Harrison et al . 1986; Abbot et al . 1994).…”
Section: Introductionmentioning
confidence: 99%